Analisis Kesalahan Ejaan Bahasa Indonesia pada Artikel Ilmiah Mahasiswa STIE Alam Kerinci - Suci Marselina (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
Abstract. This study aims to describe the use of Indonesian Spelling (EBI) in scientific articles by STIE Sakti Alam Kerinci students. This study aims to describe errors in the use of EBI in scientific articles by students. The object of research is the analysis of errors in the use of EBI in student scientific articles. The data is taken from students' errors in the use of EBI. This type of research is a qualitative descriptive research. Data were collected by observing, documenting, and writing the intralingual condalingual method. The results showed that scientific articles written by students still found several errors in the use of EBI such as errors in the use of capital letters, errors in the use of italics, errors in the use of words with affixes, errors in the use of abbreviations, and errors in the use of punctuation marks. Keywords: Spelling; scientific articles